The Impact of Green Accounting Implementation and Environmental Performance on Corporate Financial Performance - Nurfaidah, Nurfaidah; Syarifuddin, Andi; Bunyamin, Bunyamin; Hadidu, Andi (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to identify and analyze the impact of green accounting implementation and environmental performance on corporate financial performance. The population of this study is manufacturing companies in the basic industry and chemical sectors that will be listed on the Indonesia Stock Exchange in 2021-2022. The sample was selected using a purposive sampling method with three criteria, resulting in 15 companies worth observing. This study uses multiple regression analysis using the SPSS program. In this study, green accounting variables are measured using the dummy method, environmental performance variables are measured using PROPER evaluation values, and financial performance variables are measured using ROA. Based on the analysis results, it is shown that green accounting and environmental performance variables do not affect the financial performance of companies.